DEVELOPMENT OF ANIMATED LEARNING MEDIA TEXTBOOKS TO IMPROVE SKILLS IN MAKING MEDIA PROJECT - Candra Abdillah; Dameis Surya Anggara (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The research in this paper is conducted to develop a textbook product of animation- based instructional media guidelines with valid criteria in terms of content, practical use, and effectiveness in improving skills in making learning media projects for students at the Economics Education study program of Universitas Pamulang. The research methodology used is research and development (R&D) with a 4D model (define, design, develop, and disseminate). Technique and data collection instruments are product validation questionnaire sheets validated by three experts, user response sheets for practicality tests, and project assessment rubrics for effectiveness tests. Data analysis techniques used Content Validity Index (CVI), descriptive statistics, and independent sample t-test. The results reveal that 1) the product has valid criteria in content with a CVI value of 0.95, 2) products with practical use criteria with a percentage of 81.7%, and 3) products with effective criteria in improving the skills of making learning media projects with an increasing result at 36.275 in the experimental class compared to the control class at 20.720. The conclusion of the research is that the developmental product of animation-based learning media textbook guidelines is a valid criterion in terms of content, practical use, and effectively improved skills in making learning media projects.